Ranging using multicarrier signals - Li, YiHui. (2009)
This thesis aims to verify and develop a new pulse shape which is based on multi-carriers OFDM modulation techniques while implementing Modified Phased Only Correlator (MPOC) which is novel frequency domain synchronization algorithm. The new designed pulse shape is to conquer noise amplification problem which exists in Modified Phase Only Correlator (MPOC) algorithm. Furthermore, it is has illustrated that compared to cyclic prefix for guard time interval, the result shows better performance for zero padding method on the same SNR condition during our implementation. As a result, it can correctly resolve closely spaced channel paths separated by smaller SNR for zero padding method.